Influence Of Brand Communication, Brand Image And Brand Trust Through Online Media On Brand Loyalty In E-Commerce - Oetama, Seanewati (International Journal of Science, Technology & Management, 2022)
This study is the influence of brand communication, brand image and brand trust through online media on brand loyalty in e-commerce. With sampling techniques using accidental sampling techniques where sampling by way of taking by chance, by taking cases or respondents who happen to exist or are available in a place with the context of the study. The population in this study were respondents from Sampit community who use e-commerce and 140 people were taken as a sample and tested with validity test, reliability test, mediation test, hypothesis test and goodness of fit test with the help of warppls program Version 3.0.Based on the test results of the structural equation of brand communication significantly affect the online media. With the part coefficient value of 0.087 and p-value of 0.01 < 0.05 so that the hypothesis is accepted. On the test equation structural image of the brand significantly affect the online media. With the value of the part coefficientsebesar 0,606 and p-value 0,01< 0,05 so that the hypothesis is accepted. On the test equation structural brand trust significantly affect the online media. With the value of the part coefficientsebesar to 0.573 and p-value 0,01 < 0,05 so that the hypothesis is accepted. On the test equation structural brand communication significantly influence brand loyalty. With a part coefficient value of 0.100 and p-value of 0.01 < 0.05 so that the hypothesis is accepted. In the structural equation test, brand image significantly affects brand loyalty. With a part coefficient value of 0.100 and p-value of 0.01 > 0.05 so that the hypothesis is accepted. In the structural equation test, Brand Trust significantly affects brand loyalty. With a part coefficient value of 0.085 and p-value of 0.01 > 0.05 so that the hypothesis is accepted.Based on the structural equation test, brand communication significantly affects brand loyalty through online media. Because the direct influence of the coefficient value decreased from 0.57 to 0.19, this shows that the mediating variable is able to absorb the direct influence of the model without mediating, so the hypothesis is accepted.Based on the structural equation test of brand image significantly affect brand loyalty through online media. Because of the direct influence of the value of the coefficient smaller than 0,61 be 0,32, this shows that the variable pemediasi able to absorb the direct influence of the model without pemediasi, so the hypothesis is accepted.Based on the test equation structural brand trust significantly influence brand loyalty through online media. Because of the direct influence of the value of the coefficient tapers from 0.57 to 0,41, this shows that the variable pemediasi able to absorb the direct influence of the model without pemediasi, so the hypothesis is accepted. The r number of brand communication, brand image and brand confidence in online media is 0.518 or 51.8%. The remaining 48.2%. Brand communication, brand image and brand trust to brand loyalty amounted to 0.528 or 52.8%. The remaining 47.2%.